Potentially Inappropriate Screening Colonoscopy in Medicare Patients: Variation by Provider and Geographic Region - Sheffield, Kristin M. (2013)
OBJECTIVE: To determine the frequency of potentially inappropriate colonoscopy in Medicare beneficiaries in Texas and examine variation across providers and geographic regions. METHODS: This retrospective cohort study used 100% Medicare claims data for Texas and a 5% sample from the U.S. from 2000–2009. We identified Medicare beneficiaries aged ≥ 70 who received a colonoscopy from 10/01/2008–9/30/2009. A colonoscopy was classified as screening in the absence of diagnoses suggesting an indication for the procedure. A screening colonoscopy was considered potentially inappropriate on the basis of age of the patient or occurrence too soon after a normal colonoscopy. The percentage of patients undergoing a potentially inappropriate screening colonoscopy was estimated for each colonoscopy provider and Hospital Service Area. RESULTS: A large percentage of colonoscopies performed in older adults were potentially inappropriate: 23% for the overall Texas cohort, 10% in adults aged 70–75, 39% in adults aged 76–85, and 25% in adults aged ≥ 86. There was considerable variation across the 797 providers in the percent of colonoscopies performed that were potentially inappropriate. In a multilevel model including patient sex, race/ethnicity, comorbidity, education, and urban/rural residence, 73 providers had percentages significantly above the mean (24%), ranging from 29%–45% and 119 providers had percentages significantly below the mean, ranging from 7%–19%. The providers with percentages significantly above the mean were more likely to be surgeons, graduates of U.S. medical schools, medical school graduates before 1990, and higher volume providers compared to those significantly below the mean. Provider rankings were fairly stable over time (2006–07 vs. 2008–09). There was also geographic variation across Texas and the U.S., with percentages ranging from 13.3% to 34.9% in Texas. CONCLUSIONS: Many of the colonoscopies provided to older adults may be inappropriate. Receipt of potentially inappropriate colonoscopy depends in part on where patients live and what provider they see.